Seizure Control Outcomes following Resection of Cortical Dysplasia in Patients with DEPDC5 Variants: A Systematic Review and Individual Patient Data Analysis - McGinley, Christopher; Teti, Saige; Hofmann, Katherine; Schreiber, John M.; Cohen, Nathan T.; Gaillard, William D.; Oluigbo, Chima O. (Neuropediatrics, 2023)
There is insufficient evidence regarding the efficacy of epilepsy surgery in patients with pharmacoresistant focal epilepsy and coexistent DEPDC5 (dishevelled EGL-10 and pleckstrin domain-containing protein 5) pathogenic (P), likely pathogenic (LP), or variance of unknown significance (VUS) variants. To conduct a systematic review on the literature regarding the use and efficacy of epilepsy surgery as an intervention for patients with DEPDC5 variants who have pharmacoresistant epilepsy. A systematic review of the current literature published regarding the outcomes of epilepsy surgery for patients with DEPDC5 variants was conducted. Demographics and individual patient data were recorded and analyzed. Subsequent statistical analysis was performed to assess significance of the findings. A total of eight articles comprising 44 DEPDC5 patients with genetic variants undergoing surgery were included in this study. The articles primarily originated in high-income countries (5/8, 62.5%). The average age of the subjects was 10.06 ± 9.41 years old at the time of study. The most common form of epilepsy surgery was focal resection (38/44, 86.4%). Thirty-seven of the 40 patients (37/40, 92.5%) with reported seizure frequency results had improvement. Twenty-nine out of 38 patients (29/38, 78.4%) undergoing focal resection achieved Engel Score I postoperatively, and two out of four patients achieved International League Against Epilepsy I (50%). Epilepsy surgery is effective in patients with pharmacoresistant focal epilepsy and coexistent DEPDC5 P, LP, or VUS variants.
Keywords: DEPDC5; epilepsy; surgery